(untitled) (Al-Academy, 2020)
The woman represents an existential dualism with the man along history. This existence has been manifested through the history of Art starting from the arts of the old civilizations until modernism. It must be said that the history of Art refers to her presence as an extension for this history in the oriental arts, and the Arab countries including Iraq. The woman has varying outputs in terms of the content of her presence and the style of presentation. In her characterizations: maternity, fertility, femininity and others. The Iraqi artists adopted these fields among them the artist Jaber Alwan who formulated his style of presentation and its units depending on the feminine presence and his experience in her formal and stylistic field. The research consists of four chapters. The first chapter is the research methodology which includes the research problem, importance, aims, and limits, in addition to determining the terms. The research problem was the following questions: what is the space occupied by the image of the woman in the experience of the artist Jaber Alwan? Is there any stylistic specificity characterizing the image of the woman in his artistic works? Did the woman have the sovereign position in terms of form and content? Was the topic of the woman called up by the artist with its social references or with its formal ones only and what are the expressionistic dimensions for the image of the woman in his artistic works? Which woman Jaber Alwan tries to represent in his works? The importance of the research is as follows: The excavations carried out by the criticism about the presence of the woman were not outside the ranges of its expansion but their retrieval by some realistic and fictional images is in need of a reading not only on the level of concepts but also in the aesthetic field that has major problems in its interpretation. Therefore, the importance of the research is to know the data of this formation and then analyzing it and dating it whether on the level of the document or the level of the artistic presence. The aim of the research is to expose the nature and the manifestations of the image of the woman in the works of the artist Jaber Alwan.